ADOPTION OF CHILDREN WITH DISABILITIES: IMPLICATIONS FOR THE STATE - Martins, Maria Helena Venâcio; Leite, Flávia Piva Almeida [UNESP]; Leite, Lucia Pereira; DE OLIVEIRA, Taize (My University, 2023)
Objective: The study quest to portray the discovery of disability after adoption and possible implications for the State. Methodology: The study approach was qualitative, through the analysis of the current literature of the Civil Code, Brazilian Inclusion Law – LBI and the Child and Adolescent Statute – ECA. In addition, semi-structured interviews were carried out with legal guardians who carried out the adoption, and the data were interpreted by thematic content analysis. Results: The study revealed parents who only discovered the disability in living with the adopted child, in this context, the results propose the possible civil responsibility of the State in the processes of adoption of children with disabilities when the adopting family isn’t informed about the disability, understanding a failure in the National Adoption Registry. Still, clarifying the impact of lack of knowledge on disability can cause, both for children and for parents, incalculable damage, both emotionally and materially. Contributions: The study presents a critical analysis of two cases of parents by adoption and the understanding of the host institution's lack of information about the disability of the adoptees, initiating a dialogue on the attribution of appropriate civil liability.
ADOÇÃO DE CRIANÇAS COM DEFICIÊNCIA: IMPLICAÇÕES AO ESTADO
Keywords: adoption; disabilities; State responsibility